Paideia and Christianity: Priscillian’s Relation with the Late Antique Educative Milieu - Sanz Serrano, Rosa María; Díaz Bourgeal, Marina (Gerión. Revista de Historia Antigua, 2021)
This work offers a comparative analysis of the late antique schools in the Roman West and East concerning their functioning, structure, fields of study and features of their leaders, as well as the academic and political networks in which they operated. Special attention is paid to the particular cases of the emperor Julian in the East and to the Hispanic bishop Priscillian in the West, both of them educated according to the canons of classical paideia.